Fetomaternal Outcome of Eclamptic Patient in Secondary Health Care Level-3 years study (Anwer Khan Modern Medical College Journal, 2020)
Background: Eclampsia is defined as the development of seizures that cannot be attributed to other causes and /or unexplained coma during pregnancy or puerperium in a woman with pre-eclampsia. The purpose of this hospital based observational study is to evaluate the extent of the problem and to estimate the associate of foetal and maternal complicationsMethodology: The observational study was carried out Department of Obstetrics and Gynaecology in 250 bedded general Hospital Tangail from January 2015 to November 2017. All on the diagnosed patients of eclampsia were included in this study.Results: Regarding types of eclampsia 187(62.3%) patients had antepartum eclampsia, 78(26.0%) had postpartum eclampsia and 35(11.7%) had intrapartum eclampsia. Majority (57.0%) patients had 5-9 times of convulsion, 65(21.7%) had >10 times and 64(21.3%) had